PENGARUH MODEL PEMBELAJARAN NUMBERED HEAD TOGETHER (NHT) TERHADAP PRESTASI BELAJAR MATEMATIKA DITINJAU DARI KEBIASAAN BELAJAR SISWA KELAS VIII SMP N 12 YOGYAKARTA - Alexandra Yunita Kristanti; Benedictus Kusmanto (Universitas Sarjanawiyata Tamansiswa, 2015)
This research aims investigate the effect of Numbered Head Together (NHT) learning model towards students’achievement in learning mathematics based on students’ learning habit to the eighth grade students of SMP N 12 Yogyakarta in academic year 2013/2014. The population of this research was eighth grade student of SMP N 12 Yogyakarta which consist of 5 classes. The sample of the research was 2 classes which were taken by cluster sampling technique. The data were collected by using students’ learning achievement and questionnaire of learning habit. The data were analyzed by using two-way analysis of variance. The result of the research shows that (1) the students’ learning achievement who are taught using Numbered Head Together (NHT) learning model has same achievement as the students who are taught using conventional learning model, (2) the students’ learning achievement who have good habit in learning mathematics are better that the students who are not have it, (3) students’ achievement who have good learning habit in learning mathematics and are taught by using conventional learning model are better than the student who are taught by using Numbered Head Together learning model, (4) students’ achievement who have no good learning habit in mathematics and are taught by using Numbered Head Together learning model are better than the student who are taught by using conventional learning model, (5) student’ achievement in mathematics who are taught by using Head Together learning model and have good learning habit are better than the student who have no good learning habit, (6) student’ achievement in mathematics who are taught by using conventional learning model and have good learning habit are better than the student who have no good learning habit.